Multilayer films of exfoliated 2D oxide nanosheets by electrospray deposition - Moritz Nunnenkamp; Karin J. H. van den Nieuwenhuijzen; Johan E. ten Elshof (Scientific Reports, 2022)
Abstract The potential of the electrospray deposition technique as new method to make nanosheet-based multilayer films is evaluated. Densely packed nanosheet-based films with thicknesses of 1–20 nm with rms roughnesses of 2.1–2.4 nm were fabricated on samples of 1 cm2 size with a growth rate of 0.5 nm/min. Electrosprayed Ti0.87O2 nanosheet films were successfully used as oriented growth templates for 40 nm perovskite SrRuO3 thin films grown by pulsed laser deposition. The electrospray method provides a fast and easy alternative to the more commonly used Langmuir–Blodgett (LB) deposition method for nanosheet films.